Arynes in transition-metal-free multicomponent coupling reactions - Bhojgude, Sachin Suresh; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2012)
Let's couple together! The multicomponent reactions involving arynes offer direct access to unusual heterocyclic scaffolds and 1,2-disubstituted arenes. This transition-metal-free, one-pot construction of molecular complexity is likely to play a pivotal role in various carbon–carbon and carbon–heteroatom bond-forming reactions.